New terminology of medication adherence enabling and supporting activities: ENABLE terminology - Kardas, Przemyslaw; Aarnio, Emma; Agh, Tamas; van Boven, Job F. M.; Dima, Alexandra Lelia; Ghiciuc, Cristina Mihaela; Kamberi, Fatjona; Petrova, Guenka Ivanova; Nabergoj Makovec, Urska; Trečiokienė, Indrė (Frontiers in Pharmacology, 2023)
Medication non-adherence negatively affects the effectiveness of evidence-based therapies and sustainability of healthcare systems. Lack of agreed terminology of medication adherence enabling and supporting activities leads to underuse of the available tools. The ENABLE COST Action was aimed at proposing a new terminology for these activities in order to help both scientific research and its clinical application.Initial discussions within the ENABLE Working Groups allowed for the conceptualization of four interlinked terms related to adherence, i.e., 'medication adherence technology', 'medication adherence enhancing intervention', 'best practice' and 'reimbursement'. The iterative process of internal discussion was structured around two dedicated international workshops. Moreover, extensive stakeholder consultations have been organised, including an interactive online survey used to assess the level of agreement with, and the clarity of relevant terms and definitions proposed. Detailed analysis of the results of this process allowed for fine-tuning of the items, and finally, for proposing the final set of definitions. Across all the three phases of this process, the definitions were substantially modified to better reflect the concepts, simplify the language, and assure completeness and cohesiveness of terminology. Feedback obtained from the stakeholders helped this process and confirmed that the final terms and definitions were well received by the experts active in the field of medication adherence.Covering the gap in the existing terminology, this work proposes a cohesive set of terms and definitions applicable to medication adherence enabling and supporting activities. Promoting evidence-based approach to this field, this terminology may help research, clinical practice and policy.